PENGARUH BRAND AMBASSADOR DAN BRAND IMAGE ERIGO TERHADAP MINAT BELI PADA APLIKASI TIKTOK: PENGARUH BRAND AMBASSADOR DAN BRAND IMAGE ERIGO TERHADAP MINAT BELI PADA APLIKASI TIKTOKSHOP - Satria Novaldy Wibowo; Saino, Saino (Program Studi Pendidikan Tata Niaga Fakultas Ekonomika dan Bisnis Universitas Negeri Surabaya, 2024)
Advances in information technology, especially the internet, have driven significant changes in various fields,including digital marketing through social media. Platforms such as TikTok are now strategic tools to reachconsumers. One example of utilizing this strategy is Erigo, which uses brand ambassadors and brand image toincrease consumer buying interest. This study aims to analyze the influence of Erigo's brand ambassadors andbrand image on TikTok users' purchase intention. With a quantitative approach, this study involved universitystudents in Surabaya as the population, using questionnaires as data collection instruments. Data analysis wasconducted through multiple linear regression with the help of SPSS software. The results showed that both brandambassador and brand image have a significant influence on buying interest in TikTok